New additions to the list of fungi of Türkiye-3 - Asan, Ahmet; Karabıyık, Halide; Giray, Gulay (Anatolian Journal of Botany, 2024)
The book titled "List of Fungi of Türkiye", which is an important document for researchers working mycology, was published in 2020 and contains a checklist of all micro and macrofungus species recorded from Turkey. In addition, all fungal species are given Turkish scientific names in this book. In 2022 and 2024, two additional articles were prepared and the records after the publication of the book were included in these articles. With these studies, it is tried to keep the book and the checklist up to date. The present study is a continuation of these articles, and a total of 92 taxa (1 division, 3 families, 6 genera and 82 species) recorded from Türkiye by various researchers because of the literature searches have been added to the checklist. As a result of three update articles published after the publication of the book, the number of fungal species recorded in Turkey reached 6126 and the total number of taxa reached 7902. In this study, the method followed in the writing of the book was followed and Turkish scientific names were given to the 92 taxa identified as new records from Türkiye.
Keywords: Türkiye; Mantarlar; Türkçe Bilimsel İsimler; Türkiye; Mikoloji; Turkish Scientific Fungal Names; Fungi; Mycology; Fungi; Turkish Scientific Fungal Names; Türkiye